Armando, Gianfranco; Beltramo, Silvia; Cozzo, Paolo y Cuneo, Cristina (eds.): I cistercensi foglianti in Piemonte tra chiostro e corte (secoli XVI-XIX) - Maria Cristina Pascerini (Los Libros de la Corte.es)
.